Being literate in data or practices: how paradata functions in the context of literacy - Isto Huvila; Michael Olsson; Olle Sköld; Jessica Kaiser; Lisa Andersson (Information Research: An International Electronic Journal)
Introduction. Datafication of information practices underlines the importance of better understanding of data literacy and documentation. Framing data literacy as a sociocultural information practice, we draw from its conceptual affinities with the notion paradata to advance the understanding what it takes to be(come) literate, and how paradata functions in the context of literacy.